Neutrophil to lymphocyte count ratio as an early indicator of blood stream infection in the emergency department. Issue 7 (2nd September 2014) - Lowsby, Richard; Gomes, Clint; Jarman, Ian; Lisboa, Paulo; Nee, Patrick A; Vardhan, Madhur; Eckersley, Tom; Saleh, Roshan; Mills, Hannah
Abstract : Objectives: Early identification of patients with blood stream infection (BSI), especially bacteraemia, is important as prompt treatment improves outcome. The initial stages of severe infection may be characterised by increased numbers of neutrophils in the peripheral blood and depression of the lymphocyte count (LC). The neutrophil to LC ratio (NLCR) has previously been compared with conventional tests, such as C-reactive protein (CRP) and white cell count (WCC), and has been proposed as a useful marker in the timely diagnosis of bacteraemia. Methods: Data on consecutive adult patients presenting to the emergency department with pyrexial illness during the study period, November 2009 to October 2010, were analysed. The main outcome measure was positive blood cultures (bacteraemia). Sensitivity, specificity, positive and negative predictive values and likelihood ratios were determined for NLCR, CRP, WCC, neutrophil count and LC. Results: 1954 patients met the inclusion criteria. Blood cultures were positive in 270 patients, hence the prevalence of bacteraemia was 13.8%. With the exception of WCC, there were significant differences in the mean value for each marker between bacteraemic and non-bacteraemic patients (p<0.001). The area under the receiver operating characteristic curve was highest for NLCR (0.72; 95% CI 0.69 to 0.75) and LC (0.71; 0.68 to 0.74) and lowest for WCC (0.54; 0.40 to 0.57). The sensitivity and specificity of NLCR for predicting bacteraemia were 70% (64% to 75%) and 57% (55% to 60%), respectively. Positive and negative predictive values for NLCR were 0.20 (0.18 to 0.23) and 0.92 (0.91 to 0.94), respectively. The positive likelihood ratio was 1.63 (1.48 to 1.79) and the negative likelihood ratio was 0.53 (0.44 to 0.64). Conclusions: Although NLCR outperforms conventional markers of infection, it is insufficient in itself to guide clinical management of patients with suspected BSI, and it offers no advantage over LC. However, it may offer some diagnostic utility when taken into account as part of the overall assessment.